Evaluation of Eating Quality in Sensory Panelist and Instrumental Tenderness of Beef from Harar, Arsi and Bale Cattle Breeds in Oromia, Ethiopia - Birmaduma Gadisa; Yesihak Yusuf; Mohammad Yousuf (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2019)
Meat is one of the most nutritious animal products that humans can consume, particularly in terms of supplying high-quality protein, minerals and essential vitamins. Hence, the demand for meat is not only quantity wise, but also quality wise. The objective of this study was evaluate eating qualities of beef produced at public abattoirs from Arsi, Bale and Harar cattle breeds with semi-trained sensory panel evaluation and instrumental tenderness. To know the status of meat produced for domestic market in relation with globally demands. The samples were collected from the longissimus dorsi region between 12th and 13th ribs within 45 min after slaughters. The samples were packed in vacuum-seal and aged for14 days to evaluate instrumental tenderness using Warner Bratzler Shear Force Device and eating quality using panel testing. Mean values of 33.12 N, 7.12, 7.2 and 7.24 were determined in instrumental tenderness, sensory tenderness, juiciness, and flavor of beef respectively. The parameters were significantly affected by age, breeds and season interactions (P<0.01). Breed interaction with age and season exhibited significant variation (P<0.05) on water holding capacity. Beef pH was significant affected by season. The instrumental tenderness had negative medium relationship with sensory attributes conducted for tenderness and juiciness, but positive with flavor. From this study, it was concluded that quality of beef produced in study areas was relatively tender which internationally competent but becomes tough as cattle gets older. It is recommended that strategy should be developed to encourage premium payment for young cattle marketing that is not exposed to draft service and creating awareness among stakeholders on quality beef production. As Ethiopia is planning to in the beef market in the Middle East Countries, it is highly needed to promote Ethiopian beef at international markets.